Extraction of Normal characteristics and Abnormal cardiac signals using methods of Sampling techniques - Dimas Tri Anggara; Hindarto (Universitas Muhammadiyah Sidoarjo, 2019)
Health is a serious issue facing the world today. Health problems are increasingly growing with changing times. One of them is the health of the heart, so we need a data that can monitor the condition of normalcy and abnormal heartbeat of a person with the method of sampling technique, heart rate and position of a person so that later in the event of health problems that are really worrying can be quickly resolved quickly integrated with of course sending information that can receive long distance and accurate. The data obtained will be entered into the matlab for data calculation and data processing, after that the data obtained will be calculated by the sampling technique method, where this technique can diagnose the normality and abnormality characteristics of the heart signal with a percentage of almost 99% where this research can replace diagnosis of heart signals medically and then the data is sent through matlab data collection communication and entered into the database of health agencies or hospitals and can be used as a reference for the first action before a medical action is performed.